INDIVIDUAL-LEVEL EQUATIONS AND GROWTH CLASSES FOR Nectandra grandiflora NEES FROM STEM ANALYSIS - SANQUETTA, Carlos Roberto; WEBER, Saulo Henrique; FORMAGINI, Fernando; BARBEIRO, Laércio Silveira; VIEIRA, Gislaine (Scientia Agraria, 2010)
The species Nectandra grandiflora is widely distributed from the Rio Grande do Sul to Minas Gerais States and have special importance due to its potential as non-woody products. The objective of this study was to establish growth rates curves for Nectandra grandiflora through stem analysis, as well as to determine its growth rates. The following models were adjusted using the Marquardt method: Gompertz, Logistics, Chapman-Richards, Bertalanffy, Korf and Weibull, and the last one resulted in the best fit. It was established functions to estimate the base diameter as function of the DBH and the base diameter with bark as function of base diameter without bark. It was observed that the growth rings of this species were visible. The growth classes were theoretically related to the canopy coverage (open, partially shaded and shaded canopy). The species is very shade-tolerant, maintaining its growth rates when kept under shaded conditions, and accelerating its growth when achieved the upper canopy.